2000
DOI: 10.1063/1.481036
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio treatment of electron correlations in polymers: Lithium hydride chain and beryllium hydride polymer

Abstract: Correlated ab initio electronic structure calculations are reported for the polymers lithium hydride chain [LiH] ∞ and beryllium hydride [Be 2 H 4 ] ∞ . First, employing a Wannier-function-based approach, the systems are studied at the Hartree-Fock level, by considering chains, simulating the infinite polymers. Subsequently, for the model system [LiH] ∞ , the correlation effects are computed by considering virtual excitations from the occupied HartreeFock Wannier functions of the infinite chain into the compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 20 publications
1
46
1
Order By: Relevance
“…However, since the correlation effects are highly localized in real space, convergence with respect to the cluster size is rarely a problem here. Moreover, in our earlier calculations on the infinite LiH chain, 31 and the bulk LiH, 42 we had carefully compared the correlated calculations performed simultaneously on the infinite system and its finite cluster, and found excellent agreement between the two sets of results. The issue of the convergence of the present set of results with respect to the cluster size is very important, and, therefore, will be discussed again in Sec.…”
Section: Applied Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the correlation effects are highly localized in real space, convergence with respect to the cluster size is rarely a problem here. Moreover, in our earlier calculations on the infinite LiH chain, 31 and the bulk LiH, 42 we had carefully compared the correlated calculations performed simultaneously on the infinite system and its finite cluster, and found excellent agreement between the two sets of results. The issue of the convergence of the present set of results with respect to the cluster size is very important, and, therefore, will be discussed again in Sec.…”
Section: Applied Methods and Computational Detailsmentioning
confidence: 99%
“…Keeping in view these conflicting results obtained for the bond alternation from the DFT calculations, and the fact that HF results tend to overestimate ␦, we believe that a systematic study of the influence of electron-correlation effects on the bond alternation in the infinite C chain is in order. Therefore, we decided to apply our ab initio wave-function-based many-body methodology used earlier to study a number of conjugated polymers, 28,[30][31][32] to the problem of the infinite C chain as well. In addition, to put our correlated results in proper perspective, we also performed LDA calculations on the C chain using the same basis set that was used for the HF and the subsequent many-body calculations.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 This approach of computing expectation values derives its legitimacy from the generalized Hellman-Feynman theorem, and it is called "finite-field method" in quantum chemistry literature. 11 Therefore, the present set of HF and correlated calculations are distinct from our previous ones [12][13][14][15][16] in that the present calculations have been performed in the presence of an external electric field. For details related to our Wannier-function-based HF methodology, in the presence of external electric fields, we refer the reader to our earlier papers.…”
Section: Methodsmentioning
confidence: 70%
“…In our previous studies performed on ionic systems, we demonstrated that the increments can be truncated to two-body effects ͑n =2͒, with the Wannier functions not being farther than the third-nearest neighbors. 15,16 We follow the same truncation scheme here as well, with the method of correlation calculation being the full-configuration interaction as in our previous works, where other technical details related to the approach are also described. 4,5,15,16 …”
Section: Methodsmentioning
confidence: 99%
“…11,24,25,26,27 It was found, empirically, to provide accurate HartreeFock energies and band structures. 24,25,27,28 The program has also been used as a starting point for post HartreeFock calculations; the correlation energy of the ground state 11,29 and the quasiparticle band structure of several polymers and crystals have been investigated. 12,14,15,17 The idea to directly solve for Wannier-type functions has also been discussed, e.g., in Refs.…”
Section: Introductionmentioning
confidence: 99%